MOTIVES FOR STUDENTS TO BE EXPOSED TO EDUCATIONAL PROGRAMS ON TV CHANNELS (Iraqi educational channels as a model) - Abdulkareem Dawood, Hala; Hadi Hindi, Muntaha (ALBAHITH ALALAMI, 2021)
The educational function of television is one of the basic functions in light of the technical development that included the specialized satellite channels in all its fields, including the educational field, as its role became parallel to the role of educational institutions. These studies are among the descriptive studies in terms of the type of study methodology that describes the phenomenon, interprets its and extract the results and relationships between the variables. The study sample was multistage (random and intentional) included the students of the sixth academic and literary preparatory stage in the city of Baghdad.The study problem was summarized by the following main question:( What are the motives for the exposure of the students of Baghdad to the Iraqi educational channels ? What is the extent of the gratifications that have been achieved as a result of this exposure?).Leading to the secondary questions that branched from it, the most important of which are:- What are the habits and patterns of students' follow-up and educational programs in the Iraqi educational satellite channel?- What are the motives for students' exposure to educational lessons in the Iraqi educational satellite channel?- The study reached several results that can be summarized as follows:- The high degree of exposure of the student population to the Iraqi educational satellite programs, especially for the students of the completed classes, thus achieving the result of the assumption (that the audience of the recipients is an active audience and its use of the media is a deliberate use to achieve a certain benefit).- The results showed that the program plans included the preparation and broadcast of enrichment programs to address various issues and activities of interest to the student group, such as a targeted audience from the satellite channel?The results indicated the high level of utilitarian motivations at the level of ritual motives of the study sample while they were following the educational channels of Iraq, including the adoption of the interesting method of providing educational lessons, as the extent of follow-up increased exponentially with a high degree of benefit from the contents of these programs.